Uvedba novega izdelka na evropsko tržišče ob upoštevanju notranjih potencialov podjetja - Vukasovič, Tina (Management, 2014)
Development of new technologies and market saturation with products from different backgrounds with different properties for end users often causes confusion and uncertainty in the process of buying. Because of the faster flow of information, modern companies are becoming a learning societies based on open information, equality and the organizational culture that encourages collaboration, flexibility and research through the introduction of new products on the market. At the beginning, we have focused on the theoretical bases and market research with regard to knowledge management. Below, we have designed and built appropriate marketing to introduce a new product to the demanding European market. The market survey was conducted examining the internal potential of the company who gave the answer or the placement of a new product on the demanding European market economically justified and reasonable or not.
Keywords: industrijski izdelki; mednarodni trg; podjetja; raznolikost izdelkov; trženje